ACTN3 R577X gene polymorphism may play a role to determine the duration of judo matches - Itaka, T.; Tomizawa, Y.; Inoue, K.; Agemizu, K.; Aruga, S.; Machida, S, (Trends in Sport Sciences, 2017)
The alpha-actinin-3 (ACTN3) and angiotensinconverting enzyme (ACE) genes are associated with sports performance and physical fitness. In particular, gene polymorphisms in ACTN3 and ACE are reportedly related to the duration of athletic activity and swimming. Variability in the duration of judo matches may be related to genetic factors. We hypothesized that these gene polymorphisms are associated with the duration of judo contests. Aim of Study. The purpose of this study was to investigate the association between the ACTN3 and ACE gene polymorphisms and the duration of judo matches. Material and Methods. The study included 129 Japanese male athletes in the judo club of T University. The frequency of the ACTN3 R577X (rs1815739) and ACE I/D (rs1799752) polymorphisms were determined with polymerase chain reaction (PCR) or PCR-restriction fragment length polymorphism analysis. We also surveyed 13 judo instructors who had taught the study subjects. The instructors rated the speed to decide the match outcomes of the subjects. Using this data, we then divided the subjects into a fast match-decider group and a slow match-decider group and compared the genotype frequencies of these groups by using the chi-square test. Results. Genotype frequencies of the ACTN3 R577X gene polymorphism but not the ACE gene polymorphism were significantly different between fast match-decider and slow match-decider groups. The ACTN3 R577X gene polymorphism was associated with the duration of judo matches. Conclusions. The ACTN3 R577X gene polymorphism, but not the ACE I/D gene polymorphism, may be associated with the duration of judo matches.